Sex, Drugs, and TBI: The Role of Sex in Substance Abuse Related to Traumatic Brain Injuries - Oliverio, Robin; Karelina, Kate; Weil, Zachary M. (Frontiers in Neurology, 2020)
Traumatic brain injuries (TBI) are a significant public health problem costing billions of dollars in health care costs, and lost productivity while simultaneously reducing the quality of life for both patients and caregivers. Substance abuse is closely interconnected with TBI as intoxicated individuals are at a greater risk of suffering brain injuries and TBI may serve as a risk factor for the subsequent development of substance use disorders. There are also prominent sex differences in the etiology, epidemiology and consequences of TBI. For instance, men are more likely to be injured on sporting fields or in auto accidents while women are disproportionately likely to suffer TBI associated with intimate partner violence. Moreover, while men are much more likely to suffer TBI during late adolescence-young adulthood, sex differences in the incidence of TBI are much less prominent during other developmental epochs. Further, there are prominent sex differences in substance abuse biology, for example, while more men meet diagnostic criteria for substance abuse disorders, women tend to advance from casual use to addiction more quickly. In this paper, we will discuss the emerging clinical and preclinical evidence that these sex differences in TBI and substance abuse interact and may be prominent determinates of long-term outcomes.